Um estudo empírico sobre a construção da identidade social do consumidor de toy art - Barboza, Renata Andreoni (2009)
The objective of the present work is to understand how Toy Art consumer’s use their possession to build up their social identity, and also explore this consumption relationship by investigating the factors that trigger the process of extension self in Toy Art. The theoretical support of this work ocurred by a deepening of the themes already raised earlier by Campbell & Barbosa (2006) and McCracken (2003), in their studies of culture and consumption; Schouten & McAlexander (1995) in their research on subcultures of consumption; Hall (2005), who exposed his theories about the formation of identity in the modern world; Douglas & Isherwood (2004), who studied the rituals of consumption; Belk (1988), with his research on the extension self. The present study is of exploratory, character and was conducted in-depth interviews in order to let emerge the feelings and emotions of the respondents, for better orientation towards the analysis of the data. Data were collected from 14 Toys consumer’s, of both genders, aged between 19 and 38 years, live in Belo Horizonte, Minas Gerais, Rio de Janeiro, Rio Grande do Sul, São Paulo and the Distrito Federal, during the moths of July and August 2009. To achieve the proposed objectives, the research method used was qualitative, with prioritization of the subject and subjectivity, using an interpretative structure for data analysis. The results showed that Toy Art consumer’s use their possession to compose their social identity and as a form of differentiation and expression. The extension of the selves just happens during this search for the unusual, for a possession that distinguishes from other people. Conclude the work, making recommendations to management in order to benefit and develop the industry in this segment.